HUBUNGAN ORIENTASI MASA DEPAN DALAM BIDANG PENDIDIKAN DENGAN KETERATURAN DIRI DALAM BELAJAR (SELF REGULATED LEARNING) - Fifih Nurafifah; Nani N. Djamal; Fenti Hikmawati (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2009)
Future orientation on education could be called as a goal; target, plan and strategy dreamed and strived by individual to achieve. One of many strategies could be used by student to make those dreams of their future on education to become true is to have self regulation in learning style and methods. In this research we can find out that future orientation on education has a significant positive correlation with self learning regulations.